Tumor Associated Macrophages, as the Dominant Immune Cells, Are an Indispensable Target for Immunologically Cold Tumor—Glioma Therapy? - Tong, Ni; He, Zhenqiang; Ma, Yujie; Wang, Zheng; Huang, Ziming; Cao, Haihong; Xu, Lanyang; Zou, Yuheng; Wang, Wanyu; Yi, Chenpeng; Yin, Zhixin; Wang, Qirui (Frontiers in Cell and Developmental Biology, 2021)
Tumor microenvironment (TME) is the cornerstone of the occurrence, development, invasion and diffusion of the malignant Central Nerve System (CNS) tumor, glioma. As the largest number of inflammatory cells in glioma TME, tumor associated macrophages (TAMs) and their secreted factors are indispensable to the progression of glioma, which is a well-known immunologically “cold” tumor, including the growth of tumor cells, invasion, migration, angiogenesis, cancer immunosuppression and metabolism. TAMs intimately interface with the treatment failure and poor prognosis of glioma patients, and their density increases with increasing glioma grade. Recently, great progress has been made in TAM-targeting for anti-tumor therapy. According to TAMs’ function in tumorigenesis and progression, the major anti-tumor treatment strategies targeting TAMs are to hinder macrophage recruitment in TME, reduce TAMs viability or remodel TAMs phenotype from M2 to M1. Different approaches offer unique and effective anti-tumor effect by regulating the phagocytosis, polarization and pro-tumor behaviors of macrophages in the therapy of glioma. The present review summarizes the significant characteristics and related mechanisms of TAMs and addresses the related research progress on targeting TAMs in glioma.